2024
DOI: 10.1021/acs.analchem.3c04290
|View full text |Cite
|
Sign up to set email alerts
|

MOCCal: A Multiomic CCS Calibrator for Traveling Wave Ion Mobility Mass Spectrometry

Hannah M. Hynds,
Kelly M. Hines

Abstract: Ion mobility mass spectrometry (IM-MS) is a rapid, gas-phase separation technology that can resolve ions on the basis of their size-to-charge and mass-to-charge ratios. Since each class of biomolecule has a unique relationship between size and mass, IM-MS spectra of complex biological samples are organized into trendlines that each contain one type of biomolecule (i.e., lipid, peptide, metabolite). These trendlines can aid in the identification of unknown ions by providing a general classification, while more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Sample preparation. As samples, an unlabeled and a uniformly 13 C-labeled ethanolic yeast (Komagataella phaffii) extract pellet 16 were provided by Isotopic Solutions (Vienna, Austria). The yeast extract pellets were re-extracted using a lipidomics extraction based on methyl tert-butyl ether (MTBE) modified from Matyash et al 26 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample preparation. As samples, an unlabeled and a uniformly 13 C-labeled ethanolic yeast (Komagataella phaffii) extract pellet 16 were provided by Isotopic Solutions (Vienna, Austria). The yeast extract pellets were re-extracted using a lipidomics extraction based on methyl tert-butyl ether (MTBE) modified from Matyash et al 26 .…”
Section: Methodsmentioning
confidence: 99%
“…However, CCS calibrants usually have dissimilar chemical properties to analytes of interest which poses some challenges for routine 'omics workflows including lipidomics. Especially in the case of TWIM-MS lipidomics applications, it has been shown that either a calibration 12,13 or an external post-calibration correction 14 using (class-specific) lipids leads to an improved trueness of CCS values compared to DT CCS and/or published TW CCS values. Moreover, high-resolution IM analyzers including Structures for Lossless Ion Manipulation (SLIM) 15 and cyclic IMS 16 offer new possibilities for challenging lipid isomer separations for which CCS calibration provides new challenges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CCS calibrants usually have dissimilar chemical properties to analytes of interest, which poses some challenges for routine “omics” workflows, including lipidomics. Especially in the case of TWIM-MS lipidomics applications, it has been shown that either a calibration , or an external postcalibration correction using (class-specific) lipids leads to an improved trueness of CCS values compared to DT CCS and/or published TW CCS values. Moreover, high-resolution IM analyzers, including structures for lossless ion manipulation (SLIM) and cyclic IMS offer new possibilities for challenging lipid isomer separations for which a CCS calibration provides new challenges.…”
Section: Introductionmentioning
confidence: 99%